Parametric Method For Evaluating Optimal Ship Deadweight - Michalski Jan P. (Polish Maritime Research)
The paper presents a method of choosing the optimal value of the cargo ships deadweight. The method may be useful at the stage of establishing the main owners requirements concerning the ship design parameters as well as for choosing a proper ship for a given transportation task. The deadweight is determined on the basis of a selected economic measure of the transport effectiveness of ship - the Required Freight Rate (RFR). The mathematical model of the problem is of a deterministic character and the simplifying assumptions are justified for ships operating in the liner trade. The assumptions are so selected that solution of the problem is obtained in analytical closed form. The presented method can be useful for application in the pre-investment ships designing parameters simulation or transportation task studies.